Research on the flex network structure for testbeds of distribution system. (April 2020) - Wu, Lifang; Yu, Xiaoyong; Chen, Shaonan; Huang, Weixiang; Kai, Tao
Abstract: Objective: The real distribution network testbed is a testing and experiment environment for the popularization and application of new technologies, new equipment and new methods in distribution network. In order to simulate the operation of the actual distribution network as much as possible, the grid structure of the real testbed should be consistent with the actual distribution network. However, due to site conditions and investment constraints, the construction of a flexible grid structure and the conversion of different connection modes through the on-off configuration of distribution switches is the key to the construction of real distribution network testbed. Methods: This paper analyzes the structural characteristics of typical connection modes of domestic 10kV distribution lines, puts forward the decomposition and reconstruction method of typical connection modes based on unit structure, and then puts forward the grid structure of real distribution network testbed which can be switched flexibly. Results: By using the grid structure, the typical connection modes of all kinds of cables, overhead and hybrid lines, as well as the atypical connection modes with branch lines can be flexibly switched, which can meet the requirements of all kinds of tests and experiments of the real distribution network testbed. Conclusion: Based on the actual engineering example, the method proposed in this paper is scientific and effective, and provides method support for the construction scheme of real distribution network testbed.